2017
DOI: 10.12820/rbafs.v.22n2p165-175
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and fruit/vegetable intake in a sample of Brazilian university students: association with nutritional status

Abstract: The objective of this study was to identify the frequency of practice of exercise and fruit/vegetable intake in a representative sample of Brazilian university students and their possible association with nutritional status. The sample consisted of 1177 individuals of both sexes, aged 18-35 years, selected randomly. Information about the frequency of exercise and fruit/vegetable intake was obtained with the National College Health Assessment-II self-administered questionnaire. Nutritional status was defined ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…To compare the level of physical inactivity, the Shapiro-Wilks normality test was initially performed, followed by Kruskal-Wallis with Dunn's post hoc test with a 5% significance level. Like our study, other authors also found higher physical inactivity among females [29][30][31] with a consequent increase in the rates of obesity [12][13][14] , diabetes mellitus, hypercholesterolemia, metabolic syndrome, and hypertension 32 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To compare the level of physical inactivity, the Shapiro-Wilks normality test was initially performed, followed by Kruskal-Wallis with Dunn's post hoc test with a 5% significance level. Like our study, other authors also found higher physical inactivity among females [29][30][31] with a consequent increase in the rates of obesity [12][13][14] , diabetes mellitus, hypercholesterolemia, metabolic syndrome, and hypertension 32 .…”
Section: Discussionsupporting
confidence: 86%
“…From 2006 to 2017, the frequency of overweight adults increased by an average of 1.14%/year and obese adults by 0.67%/year; following this trend, the frequency of individuals diagnosed with diabetes increased by an average 0.24%/year 10 . The problems resulting from global physical inactivity are related to metabolic syndrome 11 , overweight 12,13 , and dementia 14, among others 15 .…”
Section: Introductionmentioning
confidence: 99%